Mechanisms of vaccine protection in chickens against challenge with virulent Mycoplasma synoviae - Kanishka I. Kamathewatta; Anna Kanci Condello; Pollob K. Shil; Amir H. Noormohammadi; Neil D. Young; Glenn F. Browning; Kelly A. Tivendale; Nadeeka K. Wawegama (Veterinary Research)
Abstract The Vaxsafe MS vaccine is used globally to control infections with Mycoplasma synoviae (MS) in commercial poultry. It provides long-term protective immunity against airsacculitis and tracheitis caused by M. synoviae. However, the mechanisms involved in the protection afforded by the vaccine are not well understood. This study aimed to investigate and compare tracheal mucosal responses to challenge with virulent M. synoviae in chickens vaccinated with Vaxsafe MS and in unvaccinated chickens. The tracheal mucosal transcriptional profiles were obtained using messenger RNA sequencing. Compared to the unvaccinated-unchallenged chickens, 64 genes were differentially transcribed in the vaccinated-challenged chickens and 321 genes were differentially transcribed in the unvaccinated-challenged chickens. In vaccinated-challenged chickens, functional categories enriched with up-regulated genes included IL4 production, TCR signalling (without T-cell co-stimulation), T-cell activation/proliferation/differentiation and B-cell activation/proliferation. In the unvaccinated-challenged chickens, many other functional categories were also enriched with upregulated genes, including Positive regulation of the MAPK/ERK cascades, Positive regulation of IFN gamma production, T-cell co-stimulation, Negative regulation of IL6 production, IL10 production, Toll-like receptor signalling, Neutrophil activation/degranulation, DAP12 signalling, Chemotaxis, Phagocytosis, Cell killing, PD-1 signalling, Negative regulation of non-canonical NF-κB signal transduction, Isotype switching and Somatic diversification of immune receptors. The transcriptional changes in the unvaccinated-challenged chickens were indicative of T-helper-1-cell-mediated inflammation and dysregulated primary T- and B-cell responses, which were absent in the vaccinated-challenged chickens. In the vaccinated-challenged chickens the changes were indicative of a memory T-follicular-helper-cell-dependent secondary B-cell response, suggesting that this response was protective against the dysregulated inflammatory response seen in unvaccinated chickens.